ONLINE CONSUMER BEHAVIOR DALAM KEPUTUSAN PEMBELIAN PADA APLIKASI E-COMMERCE - Husna, Arina Himatul; Faladhin, Johan; Marsya, Ulmi; Dhea, Nasya (Journal of Digital Business and Innovation Management, 2022)
The digital era has brought about a shift in consumer behaviour. This study offers an explanation for the purchasing decisions made by online shoppers using the ZALORA e-commerce platform. Exposure served to employ descriptive qualitative data collection to technique, observation, interview, and documentation. As a consequence of this, both internal and external factors have something to do with the effectiveness of consumer spending and the convenience of access. The desire and lifestyle of a person is the next factor, followed by the contribution of social media and a trend, the quality of the service, and the activities of marketing on a platform.